Development of HOTS-Based E-Modules Using Sigil Applications on Circular Motion Materials - Maria Ulfa; Imam Sucahyo (Jurnal Pendidikan Fisika, 2022)
This research aims to examine the validity, effectivenes, and practicality of HOTS-based e-modules using the Sigil application. Employing a research and development method with the ADDIE development model (analysis, design, development, implementation, and evaluation), this research involved 35 students of class X MIPA 8 at SMAN 2 Bangkalan in the academic year of 2021/2022 as the research subjects. This HOTS-based e-module development research includes a pre-experimental design type that used the one-group pre-test post-test method. The obtained data from this study were the results of HOTS-based e-module validation, pre-test results, post-test results, and students’ response data to the use of HOTS-based e-modules. In this study, it was found that the results of HOTS-based e-module validation using the Sigil application on circular motion material were 4,556 in the material aspect and 4,498 in the media aspect; both are categorized as very good. The average results of the students' pre-test and post-test were 6.46 and 70.83, respectively. The average n-gain value is 0.69, which indicates that the effectiveness of using HOTS-based e-modules using Sigil applications on circular motion material was in the medium category. The result of the students’ response questionnaire was 4.05 (good category), which indicates that the HOTS-based e-module using the Sigil application is practical. The conclusion of this study is that the development of the HOTS-based e-module using the Sigil application on circular motion material is valid and practical.